1996
DOI: 10.1007/bf01411736
|View full text |Cite
|
Sign up to set email alerts
|

CO2 and indomethacin vasoreactivity in patients with head injury

Abstract: The purpose of this study was to compare the effect of hyperventilation and indomethacin on cerebral circulation, metabolism and pressures in patients with acute severe head injury in order to see if indomethacin may act supplementary to hyperventilation. Fourteen severely head injured patients entered the study. Intracranial pressure (ICP), mean arterial blood pressure (MABP) and cerebral perfusion pressure (CPP) were monitored continuously. Within the first four days after the trauma the CO(2) and indomethac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 20 publications
(20 reference statements)
0
26
1
Order By: Relevance
“…However, the role of COX2 in the pathophysiology of TBI is uncertain. Treatments that prevent COX2 induction (glucocorticoids) or inhibit enzyme activity (indomethacin) have had, at best, equivocal success in the clinical treatment of TBI (Benedek et al, 1987;Biestro et al, 1995;Dahl et al, 1996). If, contrary to current opinion, COX2 induction were beneficial, then inhibition might result in a worsened outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of COX2 in the pathophysiology of TBI is uncertain. Treatments that prevent COX2 induction (glucocorticoids) or inhibit enzyme activity (indomethacin) have had, at best, equivocal success in the clinical treatment of TBI (Benedek et al, 1987;Biestro et al, 1995;Dahl et al, 1996). If, contrary to current opinion, COX2 induction were beneficial, then inhibition might result in a worsened outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The only tomographic study on living animals (Schumann et al, 1996), found no change of the global CMR O 2 but interestingly (see below) a small and significant increase of CMR O 2 in thalamus and pons. In adult humans, the effect of indomethacin on CMR O 2 was assessed only by the arterio-venous difference (Wennmalm et al, 1981;Jensen et al, 1991;Dahl et al, 1996;Bundgaard et al, 1996) and no significant change was observed in any of these studies. However, a study of preterm infants with near-infrared-spectroscopy of cytochrome oxidase indicated reduced oxygenation (Benders et al, 1995).…”
Section: Effect Of Indomethacin On Cmr Omentioning
confidence: 99%
“…We then tested the properties of the extended model equation by calculating the magnitude of the equation parameters, which would accurately predict the values of oxygen consumption measured in the course of drug-induced lowering of CBF. We used indomethacin, which lowers blood flow, probably by nonselectively inhibiting cyclooxygenase-1 (COX-1) and -2 (Jensen et al, 1991(Jensen et al, , 1993Dahl et al, 1996;Imberti et al, 1997;Zonta et al, 2003), although other mechanisms have also been proposed (Wang et al, 1993;Parfenova et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and clinical studies show that indomethacin acts as a potent vasoconstrictor on the cerebral vasculature [3, 4, 5, 6]. The mechanisms of the indomethacin-induced vasoconstriction are largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of therapies have been used in these patients, but unfortunately, these treatments frequently are not effective. There is increasing evidence from animal models and a few reports of patients with head trauma that indomethacin decreases elevated ICP [2, 3, 4]. Up to now, indomethacin has not been used in patients with brain edema following ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%